Benign chondroid syringoma of the orbit: an atypical location. (3rd March 2020) - Yap, Jun Fai; Madatang, Angeline; Hanafi, Hanida
ABSTRACT: A 31-year-old male with no known medical illness presented with painless left eye protrusion for the past 2 years. Radiographic features were of an extraconal superior orbital mass with no invasion of adjacent structures. The patient underwent an excisional biopsy of the left superior extraconal mass a week later. The histopathological examination revealed a well-circumscribed lobulated mass with chondroid and myxoid stroma enveloping benign bland-appearing epithelial and myoepithelial cells. These pathological features were consistent with benign chondroid syringoma of the orbit. The patient had an uneventful recovery with no active ocular complaint post-operatively. Despite chondroid syringoma of the orbit being a rare tumour, it should be considered in the differential diagnosis of periorbital masses. Excision of the tumour remains the treatment of choice with histopathological examination as the gold standard of diagnosis. Regular follow-up is warranted in view of possible local recurrence or metastasis.